HUBUNGAN PENGETAHUAN DAN SIKAP MENGENAIREGULASI PENGENDALIAN TEMBAKAU SERTA PERILAKU MEROKOK TERHADAP KEJADIAN HIPERTENSI DI KELURAHANMERUYUNG TAHUN 2022 - Muhamad Adam Eldawan (2023)
There is an increase in the prevalence of hypertension in Indonesia and West Java Province. Hypertension can occur due to direct risk factors (smoking behavior) and indirect enabling factors (regulation). This study aims to study the association between knowledge and attitudes about tobacco control regulation and smoking behavior toward hypertension in Meruyung at 2022. This study using an observational analytical method with a cross-sectional study design, with 76 samples, using consecutive sampling, and data sources from primary data. The results of the univariate analysis shows that the majority of the subjects were had insufficient knowledge about tobacco control regulation (75%), had positive attitudes about tobacco control regulation (97%), were not smokers (84%), and without hypertension (84%). The results of the bivariate analysis shows that there was no significant association between knowledge toward hypertension (p = 0.274) and there were significant associations between attitudes (p = 0.023) and smoking behavior (p = 0.000, OR = 26,667) toward hypertension. This study concludes that there were significant associations between attitudes about tobacco control regulation and smoking behavior toward hypertension, but there was no significant association between knowledge about tobacco control regulation toward hypertension